MEDIATED BY EMPLOYEE INVOLVEMENT: FACTORS AFFECTING ORGANIZATIONAL PERFORMANCE IN LOCALS BANK - Yuswardi; Antony Sentoso; Raffris (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2026)
This study aims to analyze the influence of Leadership, Recognition, Work-Life Balance, Training and Development, and Organizational Culture on Organizational Performance, with Employee Engagement as a mediating variable. The research is motivated by the critical role of employee engagement in driving productivity and organizational performance, particularly within financial institutions such as Rural Banks (BPR) in Indonesia. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the data collected from 190 BPR employees in Batam City through a structured questionnaire.The results indicate that Leadership, Recognition, and Training and Development have a positive and significant effect on Employee Engagement, which in turn significantly influences Organizational Performance. Meanwhile, Work-Life Balance and Organizational Culture show no significant effect, either directly on Employee Engagement or indirectly on Organizational Performance. These findings emphasize that human resource strategies focusing on participatory leadership, fair recognition systems, and well-planned training programs substantially contribute to improving employee engagement and organizational outcomes.This research contributes theoretically to the development of employee engagement models and practically to HR policy-making in rural banks. However, the study is limited by its geographic scope and cross-sectional design. Future research is recommended to employ a longitudinal approach and include a broader organizational context to validate and expand the current findings.